Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/antibiotics10111375
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Contamination of the Office Environment in Dental and Medical Practice

Abstract: The microbiological contamination of the environment in independent healthcare facilities such as dental and general practitioner offices was poorly studied. The aims of this study were to describe qualitatively and quantitatively the bacterial and fungal contamination in these healthcare facilities and to analyze the antibiotic resistance of bacterial pathogens identified. Microbiological samples were taken from the surfaces of waiting, consulting, and sterilization rooms and from the air of waiting room of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…After the COVID-19 pandemic, dental work in dental offices became complex [ 1 ]. The permissible spaces for the dispersion of contagious and lethal diseases between patients and dental staff has increased, new protocols and biosecurity measures were established in dental practice [ 2 ], and routine procedures such as taking dental impressions require greater care because the oral cavity is a culture medium [ 3 ] of diverse microbial flora. ,In addition, having a humid medium with adequate temperature (37 °C) promotes an optimal environment for cultivation or spread of bacteria, viruses, and spores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the COVID-19 pandemic, dental work in dental offices became complex [ 1 ]. The permissible spaces for the dispersion of contagious and lethal diseases between patients and dental staff has increased, new protocols and biosecurity measures were established in dental practice [ 2 ], and routine procedures such as taking dental impressions require greater care because the oral cavity is a culture medium [ 3 ] of diverse microbial flora. ,In addition, having a humid medium with adequate temperature (37 °C) promotes an optimal environment for cultivation or spread of bacteria, viruses, and spores.…”
Section: Introductionmentioning
confidence: 99%
“…Dental printing without disinfection can become a vehicle for cross-infection in the International Dental Federation (FDI), American Dental Association (ADA) and British Dental Association (BDA) note that dental impressions must be disinfected before casting or being transferred to the laboratory using universal post pandemic protocols recommended by the WHO [ 3 , 4 ]. Dental impressions, instruments and dental equipment are exposed to secretions and aerosols from the oral cavity (turbine water during dental surgery, saliva, blood, exudate) [ 5 , 6 ], therefore requiring disinfection protocols to counteract the activity of viruses, bacteria, fungi, spores, yeasts, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding TVOCs, the use of dental materials in the dental treatment room and the use of cleaning and disinfecting products in all the healthcare and care facilities was a major source of VOCs, but this cannot be reduced. Indeed, cleaning and disinfecting activities are crucial to limit the contamination of healthcare environments and to reduce the risk of healthcare-associated infection [ 44 , 45 ]. However, it is important to close these products when they are not being used to reduce their diffusion into the indoor air.…”
Section: Discussionmentioning
confidence: 99%
“…Water pipes are flushed with potable water of the local water supplier that rinses the DUWLs, particularly chair units and instruments. Dentists and dental staff as well as patients are exposed to aerosols on a daily basis produced by medical water-bearing instruments as high-speed turbines, air polishing systems, hand pieces, and mechanical scalers [ 1 4 ]. Several studies reported about microbiological contaminations of DUWLs [ 5 – 10 ].…”
Section: Introductionmentioning
confidence: 99%